Prospective Comparative Study of Anterior Cruciate Ligament Reconstruction Using the Double-Bundle and Single-Bundle Techniques - Song, Eun Kyoo (2009)
BACKGROUND: The intent of double-bundle anterior cruciate ligament reconstruction is to reproduce the normal anterior cruciate ligament anatomy and improve knee joint rotational stability. However, no consensus has been reached on the advantages of this technique over the single-bundle technique. HYPOTHESIS: We hypothesized that double-bundle anterior cruciate ligament reconstruction could provide better intraoperative stability and clinical outcome than single-bundle reconstruction. TYPE OF STUDY: Cohort study; Level of evidence, 2. METHODS: Forty patients with anterior cruciate ligament injury in one knee were recruited; 20 were allocated to a double-bundle anterior cruciate ligament reconstruction group and 20 to a single-bundle anterior cruciate ligament reconstruction group. Intraoperative stabilities at 30° of knee flexion were compared between the 2 groups using a navigation system. Clinical outcomes including Lysholm knee scores, Tegner activity scores, Lachman and pivot-shift test results, and radiographic stabilities were also compared between the 2 groups after a minimum of 2 years of follow-up. RESULTS: Intraoperative anterior and rotational stabilities after anterior cruciate ligament reconstruction in the double-bundle group were significantly better than those in single-bundle group (P = .020 and P < .001, respectively). Nineteen patients (95%) in each group were available at a minimum 2-year follow-up. Clinical outcomes including Lysholm knee and Tegner activity scores were similar in the 2 groups at 2-year follow-up (P > .05). Furthermore, stability results of the Lachman and pivot-shift tests, and radiologic findings at 2-year follow-up failed to reveal any significant intergroup differences (P > .05). CONCLUSION: Although double-bundle anterior cruciate ligament reconstruction produces better intraoperative stabilities than single-bundle anterior cruciate ligament reconstruction, the 2 modalities were found to be similar in terms of clinical outcomes and postoperative stabilities after a minimum of 2 years of follow-up.